2014
DOI: 10.1007/s00702-014-1308-x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased levels of repulsive guidance molecule A in association with beneficial effects of repeated intrathecal triamcinolone acetonide application in progressive multiple sclerosis patients

Abstract: Repeated intrathecal application of the sustained release steroid triamcinolone acetonide is beneficial in progressive multiple sclerosis patients. Its putative regenerative effect may involve regulation of the repulsive guidance molecule A synthesis. This protein inhibits axonal regeneration and functional recovery. Objectives were to demonstrate the efficacy of four triamcinolone applications every other day in association with repulsive guidance molecule A levels in cerebrospinal fluid. Clinical evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…This decline generally precedes neuronal recovery. One may even hypothesize that changes of free radical metabolism may trigger the observed descent of RGMa concentrations in patients with an enhancement of MS symptoms during TCA treatment [Müller et al 2014[Müller et al , 2015. However, this hypothesis warrants further investigation in combination with repeat clinical evaluation of MS patients, and assessment of further metabolic CSF substrates that are responsible for regenerative processes according to a similar signal-transduction pathway as in the case of fibrinogen generation [Aiken et al 2011].…”
Section: Discussionmentioning
confidence: 99%
“…This decline generally precedes neuronal recovery. One may even hypothesize that changes of free radical metabolism may trigger the observed descent of RGMa concentrations in patients with an enhancement of MS symptoms during TCA treatment [Müller et al 2014[Müller et al , 2015. However, this hypothesis warrants further investigation in combination with repeat clinical evaluation of MS patients, and assessment of further metabolic CSF substrates that are responsible for regenerative processes according to a similar signal-transduction pathway as in the case of fibrinogen generation [Aiken et al 2011].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the underlying research method is worth to be considered for a modification. As an alternative to this misconception, one may consider the stimulation of an existing repair system in the peripheral and central nervous system as a more promising research paradigm [115][116][117][118][119][120]. Therapeutic strategies, which antagonize the repulsive guidance molecule A (RGMa) pathway, are worth for further development in clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is hypothesized that other syndromes than PD and AD, may also respond to this approach [118,120,123,129,130]. It may restore neuronal function in the long term as a general concept for repair and may weaken efficiency of toxin exposure [46,116,117,125,126,[131][132][133]. Well designed, clinical long term trials with RGMa antagonizing approaches are urgently needed in multiple sclerosis, PD, dementia syndromes, stroke, or spinal cord injury.…”
Section: Discussionmentioning
confidence: 99%
“… Alter the permeability of blood-brain barrier (BBB): the damage of BBB is an important pathological feature of MS [ 42 , 43 ]. Studies have found that the level of RGMa in cerebrospinal fluid in patients with triamcinolone acetonide treatment (its pharmacological effect is mainly on improving the BBB permeability) is reduced, which suggested that RGMa may be involved in the pathology of MS by regulating BBB permeability in MS patients ( Table 1 ) [ 44 , 45 ]. …”
Section: Rgma As a Therapeutic Target In Cns Disordersmentioning
confidence: 99%